The Relationship Between Temperament and Characters with Physical Fitness and Pain Perception in Firefighters - Kose, Samet; Kose, Nezire; Demirdel, Ertugrul; Demirdel, Senem; Akin, Ercan (YERKURE TANITIM & YAYINCILIK HIZMETLERI A S, 2016)
Objective: Firefighting is a demanding profession which requires psychological and physical fitness. The purpose of this study was to examine the relationship between personality and other psychosocial properties, physical fitness, and pain perception in firefighters. Methods: The study participants consisted of 149 male firefighters. Participants were administered the Temperament and Character Inventory (TCI), Sensation Seeking Scale (SSS), The Impact of Events Scale-Revised (IES-R), State-Trait Anxiety Inventory (STAI), Beck Depression Inventory, and Nottingham Health Profile survey. For physical fitness measurements; participants were evaluated with physical fitness parameters such as balance, flexibility, shortening, strength and endurance, agility, speed, and strength. In order to measure balance, functional reaching and standing on one foot tests are used. Results: 90 firefighters were able to complete the study fully. Harm Avoidance, Reward Dependence, and Persistence subscales of temperament and Self-directedness, Cooperativeness, and Self-Transcendence subscales of character dimensions, Sensation Seeking Scale, Impact of the Event Scale, and STAI were found to be correlated with physical fitness measurements. No correlations were found between other psychosocial measures and physical fitness measurements (p>0.05). Psychosocial measures that were associated with pain perception were Novelty Seeking, Harm Avoidance, and Persistence subscales and Thrill and Adventure Seeking subscale of the Sensation Seeking Scale. Conclusions: Our results have shown that a significant relationship exists between different psychosocial characteristics of firefighters and their physical fitness and pain perception. This relationship supports the notion that higher psychological and physical needs would have an impact on occupational performance of firefighters.
Keywords: firefighters; temperament; character; physical fitness; pain perception